Mechanism and Modeling of Power Conversion Efficiency Degradation of Si Solar Cells Under Thermal Cycling - Changwoon Han; Seungil Park (IEEE Access, 2024)
This study investigates the degradation mechanism in the power conversion efficiency of Si solar cells under thermal cycling (TC) and explores mathematical models of the degradation curve. TC experiments were conducted for two sets of solar modules. A novel method was introduced and implemented to extract the parameters in the diode circuit model of solar cells using all experimental data points in the I-V curve. It was observed that both the series resistance and reverse saturation current increased after TC. When evaluating the increases using linear, exponential, and logarithmic functions, it was expected that the power output decreases to a range of 82 to 93 % after 5,000 TC if only the series resistance increases, while in the range of 86 to 94 % after 5,000 TC if only the reverse saturation current increases. The power drop mechanism of solar cells under TC can be attributed to the cracking of the solder layer due to TC, which increases not only the series resistance but also the reverse saturation current, resulting in drops in the power output of the solar cell. A goodness-of-fit analysis reveals that a stretched exponential model best represents the power drop function of a solar cell under TC.